2022
DOI: 10.1111/cob.12561
|View full text |Cite
|
Sign up to set email alerts
|

Sustained weight loss after duodenal–jejunal bypass liner treatment in patients with body mass index below, but not above 35 kg/m2: A retrospective cohort study

Abstract: Previous data from short term studies have shown an efficacy of the duodenal-jejunal bypass liner (DJBL) for weight loss. However, less data is available regarding weight change after device removal and possible predictors for weight loss. This is a retrospective chart review of all patients who had DJBL inserted at the University Hospital Zurich between December 2012 and June 2015. A total of 27 patients had DJBL insertion. The median BMI at baseline was 38.5 (34.0-42.2) kg/m 2 . In the 24 patients with DJBL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In contrast, no patients with a body mass index (BMI) >35 kg/m 2 (at baseline) were able to maintain or present a weight regain <7%. 21 A study evaluated the outcomes at 4 years after DJBL explantation and showed improvement in AWL, %TWL, and BMI. However, none of these parameters were significantly different compared to baseline.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…In contrast, no patients with a body mass index (BMI) >35 kg/m 2 (at baseline) were able to maintain or present a weight regain <7%. 21 A study evaluated the outcomes at 4 years after DJBL explantation and showed improvement in AWL, %TWL, and BMI. However, none of these parameters were significantly different compared to baseline.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Similar to previous research, in a multicenter open-label RCT, 24% of DJBS patients lost 15% of their body weight at 12 mo, compared to 4% of controls (odds ratio = 8.3, 95%CI: 1.8-39; P = 0.007). The inclusion of the DJBS to intense medical care was linked to greater weight loss and improvements in QoL[ 137 ]. However, significant weight recovery happens during long-term follow-up after device removal, particularly in people with BMIs larger than 35 kg/m 2 [ 138 ].…”
Section: Malabsorptive Endoscopic Proceduresmentioning
confidence: 99%